Association of social factors of the parents with the feeding practices of the child – A cross-sectional study in Bharatpur, Rajasthan (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to determine the association of social factors of the parents with the feeding practices of children aged between 2 and 5 years. Materials and Methods: It was a cross-sectional study conducted among 162 households of 182 children aged 2–5 years in Bharatpur, Rajasthan. The data were collected through a door-to-door survey. A general set of questionnaire was developed to support the study. National Family and Health Survey-IV was used to calculate the socioeconomic status of the family. Results: Breastfeeding initiation among all the children was universal. Almost all the children were breastfed up to 6 months and a small proportion of children were breastfed to 24 months. Education status and lifestyle of parents showed significant effect on the duration of breastfeeding of the child (p<0.05), while lifestyle of the parents also had an impact on the age at which supplement food was given to the child (p<0.05). Conclusion: The present study showed the effective association of lifestyle of parents with the feeding practices of the children.